MODEL OF THERMOELECTRIC DEVICE FOR HEAT IMPACT ON FEET - O. V. Evdulov; D. K. Kadirova; S. G. Magomedova; T. A. Ragimova; M. A. Khazamova (Вестник Дагестанского государственного технического университета: Технические науки)
Objectives. The aim of the study is to simulate the thermophysical processes occurring during thermal treatment procedures applied to the human foot using a technical apparatus in which a thermoelectric battery (TEB) acts as a source of heat and cold.Methods. A physical model of thermal impact on the human foot is developed by means of a device whose actuating element consists of a thermoelectric battery. Different procedural versions, varying by the zone of thermal influence as well as by the presence and absence of granulates, are considered. For the most general case, a mathematical model is constructed, based on a numerical solution of the nonstationary heat conduction problem of a layered system. As a numerical method for solving a system of differential equations, the Galerkin method, characterised by high accuracy and efficiency, is used.Results. The graphs of the temperature variation dependency on the “device-foot” system thickness for various heat flow values are obtained, as well as the temperature changes of system individual parts over time and the temperature distribution along the thickness of the foot for various values of the summand determining the looseness of its contact with the granulate.Conclusion. The developed model of a thermoelectric device for thermal action on the foot area allows a comprehensive study of the heat exchange processes during physiotherapeutic procedures to be be carried out, a thermoelectric battery with the required characteristics to be selected as well as the modes of device's operation to be determined. It is established that the duration of the steady-state output of all points of the “device-biological object” system determines the acceptable inertial properties of the device. When a granulate is used during the procedures, it is necessary to take into account the power losses when selecting the thermoelectric battery power modes.